No evidence for activation of TH1 or TH17 pathways in unstimulated peripheral blood mononuclear cells from children with β-cell autoimmunity or T1D - Jenny Walldén (Dove Medical Press, 2008)
Jenny Walldén1, Jarno Honkanen2, Jorma Ilonen3, Johnny Ludvigsson1, Outi Vaarala21Linköping University, Faculty of Health Sciences, Department of Clinical and Experimental Medicine, Division of Pediatrics and Diabetes Research Center, Linköping, Sweden; 2Department of Viral Diseases and Immunology, Laboratory for Immunobiology, National Public Health Institute, Helsinki, Finland; 3Department of Clinical Microbiology, University of Kuopio, Kuopio and Immunogenetics Laboratory, University of Turku, Turku, FinlandIntroduction: The balance between TH1, TH2, TH17, and regulatory T cells has been suggested to be disturbed in type 1 diabetes (T1D). We investigated this balance in peripheral blood mononuclear cells (PBMC) from children at risk of developing T1D and children with T1D.Methods: We studied PBMC expression levels of markers related to TH1 (T-bet, IL-12Rβ1, IL-12Rβ2), TH2 (GATA-3, IL-4Rα), TH17 (IL-17A), and regulatory T cells (Foxp3, ICOS, and CTLA-4) with real-time polymerase chain reaction from 17 children with T1D, 13 children with β-cell autoimmunity, 15 children with T1D risk-associated human leukocyte antigen (HLA) haplotypes, and 24 healthy, control children.Results: We observed decreased expression levels of GATA-3 by PBMC of healthy children with autoantibodies compared to healthy, control children (p = 0.014) or children with HLA risk alleles (p = 0.032). Children with T1D demonstrated lower expression levels of T-bet, IL-12Rβ1, and IL-4Rα both at diagnosis and 12 months later.Conclusion: We found no indication of aberrant activation of TH1, TH17, or Treg in peripheral blood from children with or without risk of T1D. The observed immunological differences between children at risk of and with T1D should be considered when immunopathogenesis of β-cell destruction is studied.Keywords: transcription factor, type 1 diabetes, mononuclear cells